2018
DOI: 10.1017/s0954579418000470
|View full text |Cite
|
Sign up to set email alerts
|

An experimental test of the fetal programming hypothesis: Can we reduce child ontogenetic vulnerability to psychopathology by decreasing maternal depression?

Abstract: Maternal depression is one of the most common prenatal complications, and prenatal maternal depression predicts many child psychopathologies. Here, we apply the fetal programming hypothesis as an organizational framework to address the possibility that fetal exposure to maternal depressive symptoms during pregnancy affects fetal development of vulnerabilities and risk mechanisms, which enhance risk for subsequent psychopathology. We consider four candidate pathways through which maternal prenatal depression ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 63 publications
(88 citation statements)
references
References 219 publications
(253 reference statements)
3
83
0
Order By: Relevance
“…This pattern of findings converges with a larger adolescent literature further supporting that alterations in gray matter volume may reflect transdiagnostic risk emerging in school age (Aoki et al, 2014;Cole et al, 2014;Davis et al, 2018;Haijma et al, 2013;Niendam et al, 2012;Shang et al, 2014;Wise et al, 2017). Furthermore, these patterned alterations in gray matter volume suggest that irritability during school age predicts neurodevelopmental outcomes at preadolescence (Kaczkurkin, Moore, et al, 2019).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This pattern of findings converges with a larger adolescent literature further supporting that alterations in gray matter volume may reflect transdiagnostic risk emerging in school age (Aoki et al, 2014;Cole et al, 2014;Davis et al, 2018;Haijma et al, 2013;Niendam et al, 2012;Shang et al, 2014;Wise et al, 2017). Furthermore, these patterned alterations in gray matter volume suggest that irritability during school age predicts neurodevelopmental outcomes at preadolescence (Kaczkurkin, Moore, et al, 2019).…”
Section: Discussionsupporting
confidence: 77%
“…These changes in gray matter volume may provide critical insight into development of psychopathology, as volumes also peak in pre-adolescence (Giedd et al, 1999(Giedd et al, , 2012, which is when symptoms stabilize. In adulthood, gray matter volume is predictive of transdiagnostic psychopathology, i.e., both internalizing and externalizing symptoms (Aoki et al, 2014;Davis et al, 2018;Haijma et al, 2013;Shang et al, 2014;Wise et al, 2017). Critically, changes in gray matter volume from preschool to a peak in pre-adolescence may reflect critical neurodevelopmental trajectories and provide insight into how irritability may reflect and impact neurodevelopment (Kaczkurkin, Moore, et al, 2019).…”
Section: Irritability Predits Clinical Outcomes/gray Matter Volumesmentioning
confidence: 99%
“…Study designs involving children conceived by in vitro fertilization who were not genetically related to their mothers, or research on monozygotic twins who differ as to whether they share a placenta, indicate that the prenatal environment contributes to subsequent child development beyond effects of genetics (N. Jacobs, Van Gestel, et al, 2001;Lewis, Rice, Harold, Collishaw, & Thapar, 2011). Also, experimental designs that seek to reduce maternal prenatal stress and distress can be used to examine later outcomes and processes in offspring neurodevelopment and risk to psychopathology (Davis, Hankin, Swales, & Hoffman, 2018). We showed that aspects of the child's postnatal environment, such as maternal perceived stress, maternal depression, and SES do not account for study findings.…”
Section: Discussionmentioning
confidence: 99%
“…These past findings of more transdiagnostic transmission are consistent with latent dimensional models of psychopathology as opposed to conferring risk to depression specifically. Recent research shows associations between maternal depression and youth symptoms as assessed across levels: Maternal depression was associated with offspring depression as DSM-based syndrome, traditional Achenbach measures of internalizing (and externalizing), and the pfactor and internalizing specific latent factors (Davis, Hankin, Swales, & Hoffman, 2018). Similar findings with respect to the intergenerational effect of maternal psychopathology were found by Martel and colleagues (2016), who showed that a parental p factor associated with p-factor in offspring, and by Starr and colleagues (2014), who found the latent factor of internalizing psychopathology was significantly related between mother and child.…”
Section: Maternal Depressionmentioning
confidence: 99%